Required Separation to Mitigate Pounding of Adjacent Building Blocks - Masmoum, M. S.; Alama, M. S. A. (Engineering, Technology & Applied Science Research, 2018)
This research discusses the feasibility of using the required minimum separation distance based on SBC 301-2007. Moment resistance frames were designed with expansion joints requiring 400mm separation distance. Nonlinear response history analysis was conducted with four ground motions selected and scaled to match the risk-targeted response spectrum of NEOM city based on ASCE 7-16 provisions. An equivalent spring constant value based on floor lateral stiffness was selected as a gap link stiffness. Finally, an evaluation for the pounding response of adjacent blocks is presented along with the conclusions.